Modulating epigenome by soybean bioactive compounds in breast cancer chemoprevention - Toh, Ivan Yi Qing (2016)
For years, researchers have been puzzled by the fact why Asian women tend to have a lower breast cancer rate as compared to the American women. In the past few decades, genistein was found to be linked to this trend. However, the mystery of why Asian women have an increased in breast cancer rate when they migrated over to the western region of the world is still unsolved. We hypothesised that the bioactive genistein modulates the epigenome to lower the risk of breast cancer. A series of assays were performed on MDA-MB-231 cell line in 3 different conditions of control, treated and withdrawn to study the effect of genistein. By comet assay, we observed greater DNA damage in genistein withdrawn cells as shown by higher olive tail moment and tail moment of 15.32 and 34.57 respectively. However, the values for control and treated samples are both below 10.00 for olive tail moment and tail moment. These results indicate that the soybean genistein modulates epigenome by changing the chromatin structure which leads to change in DNA structure as observed in the comet assay. Further study is needed to uncover the underlying mechanism on how this epigenetic change is induced by genistein.